COVID-19 Pandemic and Stock Market Response: The Role of COVID-induced Fear, Investor Attention, and Firm-specific Characteristics - Sahil Narang; Savita; Rudra P. Pradhan; Bhanwar Singh (Asian Academy of Management Journal, 2023)
The study examines the reaction of S&P BSE 500 companies to the outbreak of the 2019 novel coronavirus (COVID-19). The impact of COVID-19 induced fear of volatility index (VIX) on stock market returns and the role of pre-pandemic firm-specific characteristics in intensifying/reducing the effect of fear on stock returns are analysed. Event study methodology and panel data approach with firm and industry-time fixed effects are employed. The results show fear of VIX plays a significant role in the downfall and subsequent recovery of the stock market. It is witnessed the role of pre-pandemic firm- specific characteristics is heterogeneous in intensifying/reducing the effect of fear on stock returns. Investor attention (Google search volume) and the growth of COVID-19 cases are also crucial to the stock market movements during the study period.